Daughter's Day Blues - Pegram, Laura (USA, 2000)
Phyllis Mae thinks that her little brother gets too much attention, so her Nana and Momma decide to have a special Daughter's Day celebration
Keywords: Family; Juvenile Fiction; People & Places; United State of America